Preparation method of viscose-based fiber thermal insulation composite material
By densifying, oxidizing and silicon carbide coating the viscose-based fibers, high-strength carbon fibers are formed, which solves the problem of insufficient mechanical strength of carbon fibers at high temperatures, significantly improves its mechanical properties and binding force, and improves the insulation composite material overall performance.
Patent Information
- Application Number
- CN202411512964.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-17
AI Technical Summary
The existing carbon fiber insulation materials have insufficient mechanical strength and poor binding force at high temperatures, which affects their application performance in high-temperature equipment.
Viscose-based fibers are used as raw materials, and after densification, preoxidation, surface coating, carbonization and graphitization, high-strength carbon fibers are formed, and silicon carbide whiskers and silicon carbide coatings are grown on the surface of the carbon fiber to improve the fibers. mechanical properties.
It significantly improves the mechanical strength and mechanical properties of carbon fibers, enhances the binding force between fibers and phenolic resins, and improves the overall mechanical properties and thermal insulation properties of composite materials.
Smart Images

Figure BDA0005105926560000101 
Figure BDA0005105926560000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation materials, in particular to a method for preparing a viscose-based fiber thermal insulation composite material. Background Art
[0002] Carbon fiber is formed by stacking organic fibers such as flake graphite microcrystals along the axial direction of the fiber. The microcrystalline graphite material obtained by carbonization and graphitization is a new type of fiber material with high modulus fiber. Carbon fiber thermal insulation material has excellent properties such as small thermal conductivity, low heat capacity, small linear expansion coefficient, constant mechanical strength at high temperature, corrosion resistance, and lightweight. It is widely used in high-temperature vacuum furnaces or inert atmosphere furnaces due to its superior high temperature resistance, high temperature thermal insulation performance, easy molding and processing performance, and low impurity content. At present, carbon fiber thermal insulation materials are divided into three categories according to the type of raw materials: polyacrylonitrile (PAN)-based carbon fiber thermal insulation materials, viscose-based carbon fiber thermal insulation materials, and asphalt-based carbon fiber thermal insulation materials. In terms of thermal insulation performance, viscose-based carbon fiber has the best thermal insulation performance, and the quality of thermal insulation performance directly affects the operating process and energy consumption of high-temperature equipment. The present invention provides a preparation method of a viscose-based fiber thermal insulation composite material. Summary of the invention
[0003] The invention relates to a method for preparing a viscose-based fiber thermal insulation composite material, the preparation method comprising the following steps: using viscose raw fibers as raw materials, performing densification treatment, pre-oxidation, and surface coating to obtain high-strength viscose-based carbon fibers, compounding the viscose-based carbon fibers with a carbon source precursor, and performing carbonization and graphitization treatment to prepare a thermal insulation composite material; the carbon fibers obtained by the invention have good mechanical strength and retention performance in a carbon layer, and the obtained thermal insulation composite material has excellent mechanical properties.
[0004] A method for preparing a viscose-based fiber thermal insulation composite material, the method comprising:
[0005] 1) Take viscose raw silk, place it in a tubular furnace, calcine it at high temperature under nitrogen protection to remove impurities, then pass a mixed gas of methane and nitrogen into it, and deposit carbon at high temperature to obtain surface densified carbon fiber;
[0006] 2) A mixture of water vapor and nitrogen is introduced into a tube furnace for high-temperature oxidation;
[0007] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, growing silicon carbide whiskers on the surface of the carbon fiber, and obtaining a carbon fiber with silicon carbide whiskers deposited on the surface;
[0008] 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane, taken out and dried, placed in a tube furnace, and calcined at high temperature under nitrogen protection to obtain silicon carbide-coated carbon fiber;
[0009] 5) placing the carbon fiber obtained in step 4 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, and growing silicon carbide whiskers on the surface of the silicon carbide coating layer;
[0010] 6) mixing resorcinol, formaldehyde, deionized water and sodium carbonate to obtain a phenolic resin precursor solution; mixing the carbon fiber obtained in step 5 with the precursor solution, heating to prepare a gel, and drying to obtain a xerogel;
[0011] 7) placing the dry gel from step 6 in a tubular furnace, carbonizing it at high temperature under nitrogen protection, and then graphitizing it at high temperature under nitrogen protection to obtain a viscose-based fiber thermal insulation composite material.
[0012] Furthermore, in step 1, viscose raw silk is taken, put into a tubular furnace, nitrogen is introduced, the temperature is raised to 1000-1200°C, and high-temperature calcination is performed for 2-4 hours to remove impurities, and then a mixture of methane and nitrogen is introduced, wherein methane accounts for 40-55% of the volume of the mixed gas, and the pressure in the furnace is adjusted to 1.5-3.0Mpa, and high-temperature calcination is performed for 6-10 hours to obtain surface densified carbon fiber.
[0013] Furthermore, in step 2, the temperature in the tube furnace is lowered to 800-900° C., and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 15-25% of the volume of the mixed gas. The mixture is kept at this temperature for 2-4 hours, and then cooled to room temperature and taken out.
[0014] Furthermore, in the step 3, the product of step 2 is placed in a plasma chemical vapor deposition device, a mixed gas of tetramethylsilane and hydrogen is used as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10-15%, the working temperature is 800-900°C, the working gas pressure is 100Pa, the plasma power is 100W-150W, and the growth time is 30-60min, silicon carbide whiskers are grown on the surface of the carbon fiber, and carbon fiber with silicon carbide whiskers deposited on the surface is obtained.
[0015] Furthermore, in step 4, the carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1000-1200, wherein the concentration of polycarbosilane is 8-10wt%, taken out and dried, placed in a tubular furnace, introduced with nitrogen, heated to 1400-1500°C, and calcined at high temperature for 6-10h to obtain silicon carbide-coated carbon fiber.
[0016] Furthermore, in step 5, the carbon fiber obtained in step 4 is placed in a plasma chemical vapor deposition device again, and a mixed gas of tetramethylsilane and hydrogen is used as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10-15%, the working temperature is 800-900°C, the working gas pressure is 100Pa, the plasma power is 100W-150W, and the growth time is 30-60min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating.
[0017] Furthermore, in the step 6, resorcinol, formaldehyde, deionized water and sodium carbonate are mixed uniformly in a molar ratio of 1:2:15-20:0.001-0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 5 and the precursor solution are mixed in a mass ratio of 1:3-4, and then vacuumed to a vacuum degree of more than 0.05Mpa, heated at 50-60°C for 20-30h to obtain a gel, and dried at 100°C to obtain a dry gel.
[0018] Furthermore, in step 7, the dry gel of step 6 is placed in a tubular furnace, nitrogen is introduced, the temperature is raised to 1200-1400° C., high-temperature carbonization is performed for 10-16 hours, and then the temperature is raised to 1800-2000° C., high-temperature graphitization is performed for 0.5-1 hour to obtain a viscose-based fiber thermal insulation composite material.
[0019] A viscose-based fiber thermal insulation composite material is prepared by the method described.
[0020] Beneficial technical effects of the present invention
[0021] 1) The viscose-based fibers are modified by carbon deposition under high temperature and high pressure, so that the carbon produced by methane cracking can be deposited in the pores of the viscose-based carbon fibers, thereby improving the density of the fibers;
[0022] 2) The carbon fiber is oxidized at high temperature in a water vapor environment to form a large number of oxygen-containing groups on the surface. Then, in plasma deposition, the silicon carbide fiber and the oxygen-containing groups can be closely combined to grow silicon carbide whiskers on the surface of the carbon fiber. In the subsequent silicon carbide coating process, the whiskers can produce an anchoring effect in the coating layer, thereby improving the bonding force between the carbon fiber and the silicon carbide coating layer, thereby improving the mechanical properties of the carbon fiber;
[0023] 3) Optionally, silicon carbide whiskers can be further grown on the surface of silicon carbide to utilize the anchoring effect to enhance the bonding force between the fiber and the porous carbon formed by the phenolic resin, thereby improving the mechanical properties of the composite material. DETAILED DESCRIPTION
[0024] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0025] Embodiment 1:
[0026] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, heat it to 1000°C, calcine it at high temperature for 4 hours to remove impurities, then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 40% by volume of the mixed gas, adjust the pressure in the furnace to 3.0 MPa, and calcine it at high temperature for 10 hours to obtain surface densified carbon fiber;
[0027] 2) The temperature in the tube furnace is lowered to 800°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 15% by volume of the mixed gas. The mixture is kept at this temperature for 4 hours, and then cooled to room temperature and taken out;
[0028] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10%, the working temperature is 800° C., the working pressure is 100 Pa, the plasma power is 100 W, and the growth time is 60 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0029] 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1000, wherein the concentration of polycarbosilane is 8wt%, taken out and dried, placed in a tube furnace, introduced with nitrogen, heated to 1400° C., and calcined at high temperature for 10 hours to obtain silicon carbide-coated carbon fiber;
[0030] 5) placing the carbon fiber obtained in step 4 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10%, the working temperature is 800° C., the working pressure is 100 Pa, the plasma power is 100 W, the growth time is 60 min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating;
[0031] 6) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:15:0.001 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 5 and the precursor solution are mixed in a mass ratio of 1:3, and then vacuumed to a vacuum degree of 0.05 MPa, heated at 50° C. for 30 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0032] 7) The dry gel of step 6 is placed in a tubular furnace, nitrogen is introduced, the temperature is raised to 1200°C, high temperature carbonization is performed for 16 hours, and then the temperature is raised to 1800°C, high temperature graphitization is performed for 1 hour, and a viscose-based fiber thermal insulation composite material is obtained.
[0033] Embodiment 2:
[0034] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1200°C, calcine at high temperature for 2 hours to remove impurities, and then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 55% by volume of the mixed gas, adjust the pressure in the furnace to 3.0 MPa, and calcine at high temperature for 6 hours to obtain surface densified carbon fiber;
[0035] 2) The temperature in the tube furnace is lowered to 900°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 25% by volume of the mixed gas. The mixture is kept at this temperature for 2 hours, and then cooled to room temperature and taken out;
[0036] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 15%, the working temperature is 900° C., the working pressure is 100 Pa, the plasma power is 150 W, and the growth time is 30 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0037] 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1200, wherein the concentration of polycarbosilane is 10wt%, taken out and dried, placed in a tube furnace, nitrogen is introduced, the temperature is raised to 1500° C., and high-temperature calcined for 6 hours to obtain silicon carbide-coated carbon fiber;
[0038] 5) placing the carbon fiber obtained in step 4 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 15%, the working temperature is 900° C., the working pressure is 100 Pa, the plasma power is 150 W, the growth time is 30 min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating;
[0039] 6) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:20:0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 5 and the precursor solution are mixed in a mass ratio of 1:4, and then vacuumed to a vacuum degree of 0.05 MPa, heated at 60° C. for 20 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0040] 7) placing the dry gel in step 6 in a tubular furnace, introducing nitrogen, heating to 1400° C., high-temperature carbonization for 10 h, then heating to 2000° C., high-temperature graphitization for 0.5 h, to obtain a viscose-based fiber thermal insulation composite material.
[0041] Embodiment 3:
[0042] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1100°C, calcine at high temperature for 3 hours to remove impurities, and then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 50% by volume of the mixed gas, adjust the pressure in the furnace to 2.0 MPa, and calcine at high temperature for 8 hours to obtain surface densified carbon fiber;
[0043] 2) The temperature in the tube furnace is lowered to 850°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 20% by volume of the mixed gas. The mixture is kept at this temperature for 3 hours, and then cooled to room temperature and taken out;
[0044] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, and the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0045] 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1100, wherein the concentration of polycarbosilane is 9wt%, taken out and dried, placed in a tube furnace, introduced with nitrogen, heated to 1450° C., and calcined at high temperature for 8 hours to obtain silicon carbide-coated carbon fiber;
[0046] 5) placing the carbon fiber obtained in step 4 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating;
[0047] 6) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:18:0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 5 and the precursor solution are mixed in a mass ratio of 1:3.5, and then vacuumed to a vacuum degree of more than 0.05 MPa, heated at 55° C. for 25 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0048] 7) The dry gel in step 6 is placed in a tubular furnace, nitrogen is introduced, the temperature is raised to 1300° C., and high-temperature carbonization is performed for 12 h, and then the temperature is raised to 1900° C. and high-temperature graphitization is performed for 0.8 h to obtain a viscose-based fiber thermal insulation composite material.
[0049] Example 4
[0050] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1200°C, calcine at high temperature for 4 hours to remove impurities, and then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 55% by volume of the mixed gas, adjust the pressure in the furnace to 3.0 MPa, and calcine at high temperature for 10 hours to obtain surface densified carbon fiber;
[0051] 2) The temperature in the tube furnace is lowered to 800°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 15% by volume of the mixed gas. The mixture is kept at this temperature for 2 hours, and then cooled to room temperature and taken out;
[0052] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10%, the working temperature is 800° C., the working pressure is 100 Pa, the plasma power is 100 W, and the growth time is 30 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0053] 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1000, wherein the concentration of polycarbosilane is 8wt%, taken out and dried, placed in a tube furnace, introduced with nitrogen, heated to 1400° C., and calcined at high temperature for 6 hours to obtain silicon carbide-coated carbon fiber;
[0054] 5) placing the carbon fiber obtained in step 4 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10%, the working temperature is 800° C., the working pressure is 100 Pa, the plasma power is 100 W, the growth time is 30 min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating;
[0055] 6) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:15:0.001 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 5 and the precursor solution are mixed in a mass ratio of 1:3, and then vacuumed to a vacuum degree of more than 0.05 MPa, heated at 50° C. for 20 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0056] 7) The dry gel in step 6 is placed in a tubular furnace, nitrogen is introduced, the temperature is raised to 1200° C., and high-temperature carbonization is performed for 10 h, and then the temperature is raised to 1800° C. and high-temperature graphitization is performed for 0.5 h to obtain a viscose-based fiber thermal insulation composite material.
[0057] Comparative Example 1 (without whisker deposition)
[0058] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1100°C, calcine at high temperature for 3 hours to remove impurities, and then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 50% by volume of the mixed gas, adjust the pressure in the furnace to 2.0 MPa, and calcine at high temperature for 8 hours to obtain surface densified carbon fiber;
[0059] 2) The temperature in the tube furnace is lowered to 850°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 20% by volume of the mixed gas. The mixture is kept at this temperature for 3 hours, and then cooled to room temperature and taken out;
[0060] 3) The carbon fiber obtained in step 2 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1100, wherein the concentration of polycarbosilane is 9wt%, taken out and dried, placed in a tube furnace, introduced with nitrogen, heated to 1450° C., and calcined at high temperature for 8 hours to obtain silicon carbide-coated carbon fiber;
[0061] 4) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:18:0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 3 and the precursor solution are mixed in a mass ratio of 1:3.5, and then vacuumed to a vacuum degree of more than 0.05 MPa, heated at 55° C. for 25 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0062] 5) placing the dry gel in step 4 in a tubular furnace, introducing nitrogen, heating to 1300° C., high-temperature carbonization for 12 h, then heating to 1900° C., high-temperature graphitization for 0.8 h, to obtain a viscose-based fiber thermal insulation composite material.
[0063] Comparative Example 2 (without silicon carbide coating)
[0064] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1100°C, calcine at high temperature for 3 hours to remove impurities, and then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 50% by volume of the mixed gas, adjust the pressure in the furnace to 2.0 MPa, and calcine at high temperature for 8 hours to obtain surface densified carbon fiber;
[0065] 2) The temperature in the tube furnace is lowered to 850°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 20% by volume of the mixed gas. The mixture is kept at this temperature for 3 hours, and then cooled to room temperature and taken out;
[0066] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, and the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0067] 4) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:18:0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 3 and the precursor solution are mixed in a mass ratio of 1:3.5, and then vacuumed to a vacuum degree of more than 0.05 MPa, heated at 55° C. for 25 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0068] 5) placing the dry gel in step 4 in a tubular furnace, introducing nitrogen, heating to 1300° C., high-temperature carbonization for 12 h, then heating to 1900° C., high-temperature graphitization for 0.8 h, to obtain a viscose-based fiber thermal insulation composite material.
[0069] Comparative Example 3 (no densification treatment)
[0070] 1) Take the viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1100°C, and calcine it at high temperature for 3 hours to remove impurities;
[0071] 2) The temperature in the tube furnace is lowered to 850°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 20% by volume of the mixed gas. The mixture is kept at this temperature for 3 hours, and then cooled to room temperature and taken out;
[0072] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, and the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0073] 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1100, wherein the concentration of polycarbosilane is 9wt%, taken out and dried, placed in a tube furnace, introduced with nitrogen, heated to 1450° C., and calcined at high temperature for 8 hours to obtain silicon carbide-coated carbon fiber;
[0074] 5) placing the carbon fiber obtained in step 4 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating;
[0075] 6) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:18:0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 5 and the precursor solution are mixed in a mass ratio of 1:3.5, and then vacuumed to a vacuum degree of more than 0.05 MPa, heated at 55° C. for 25 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0076] 7) The dry gel in step 6 is placed in a tubular furnace, nitrogen is introduced, the temperature is raised to 1300° C., and high-temperature carbonization is performed for 12 h, and then the temperature is raised to 1900° C. and high-temperature graphitization is performed for 0.8 h to obtain a viscose-based fiber thermal insulation composite material.
[0077] Comparative Example 4 (no oxidation process)
[0078] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1100°C, calcine at high temperature for 3 hours to remove impurities, and then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 50% by volume of the mixed gas, adjust the pressure in the furnace to 2.0 MPa, and calcine at high temperature for 8 hours to obtain surface densified carbon fiber;
[0079] 2) placing the product of step 1 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, and the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0080] 3) The carbon fiber obtained in step 2 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1100, wherein the concentration of polycarbosilane is 9wt%, taken out and dried, placed in a tube furnace, introduced with nitrogen, heated to 1450° C., and calcined at high temperature for 8 hours to obtain silicon carbide-coated carbon fiber;
[0081] 4) placing the carbon fiber obtained in step 3 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating;
[0082] 5) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:18:0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 4 and the precursor solution are mixed in a mass ratio of 1:3.5, and then vacuumed to a vacuum degree of more than 0.05 MPa, heated at 55° C. for 25 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0083] 6) placing the dry gel in step 5 in a tubular furnace, introducing nitrogen, heating to 1300° C., high-temperature carbonization for 12 h, then heating to 1900° C., high-temperature graphitization for 0.8 h, to obtain a viscose-based fiber thermal insulation composite material.
[0084] Comparative Example 5 (Whiskers not deposited on the silicon carbide surface)
[0085] 1) Take viscose raw silk, put it into a tubular furnace, introduce nitrogen, raise the temperature to 1100°C, calcine at high temperature for 3 hours to remove impurities, and then introduce a mixed gas of methane and nitrogen, wherein methane accounts for 50% by volume of the mixed gas, adjust the pressure in the furnace to 2.0 MPa, and calcine at high temperature for 8 hours to obtain surface densified carbon fiber;
[0086] 2) The temperature in the tube furnace is lowered to 850°C, and a mixture of water vapor and nitrogen is introduced, wherein the water vapor accounts for 20% by volume of the mixed gas. The mixture is kept at this temperature for 3 hours, and then cooled to room temperature and taken out;
[0087] 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 12%, the working temperature is 850° C., the working pressure is 100 Pa, the plasma power is 120 W, and the growth time is 40 min, and silicon carbide whiskers are grown on the surface of the carbon fiber to obtain a carbon fiber with silicon carbide whiskers deposited on the surface;
[0088] 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1100, wherein the concentration of polycarbosilane is 9wt%, taken out and dried, placed in a tube furnace, introduced with nitrogen, heated to 1450° C., and calcined at high temperature for 8 hours to obtain silicon carbide-coated carbon fiber;
[0089] 5) resorcinol, formaldehyde, deionized water, and sodium carbonate are mixed uniformly in a molar ratio of 1:2:18:0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 4 and the precursor solution are mixed in a mass ratio of 1:3.5, and then vacuumed to a vacuum degree of more than 0.05 MPa, heated at 55° C. for 25 h to obtain a gel, and dried at 100° C. to obtain a xerogel;
[0090] 6) placing the dry gel in step 5 in a tubular furnace, introducing nitrogen, heating to 1300° C., high-temperature carbonization for 12 h, then heating to 1900° C., high-temperature graphitization for 0.8 h, to obtain a viscose-based fiber thermal insulation composite material.
[0091] Test Data
[0092] The product performances of the embodiments and comparative examples of the present invention were tested, and the results are shown in Table 1.
[0093] Table 1
[0094]
[0095]
[0096] It can be seen from the embodiments and comparative examples that, under the condition of almost the same density, the preparation method of the present invention mainly affects the mechanical properties of the material. Under the same density, the mechanical properties are basically improved by more than 25%. It can be seen from the comparison between the embodiments and comparative examples 1 and 5 that silicon carbide whiskers are grown on the surface of the carbon fiber, so that in the subsequent silicon carbide coating process, the above whiskers can produce an anchoring effect in the coating layer; silicon carbide whiskers can also be further grown on the silicon carbide surface, and the anchoring effect is used to improve the bonding force between the fiber and the porous carbon formed by the phenolic resin, thereby improving the mechanical properties of the composite material. By comparing the embodiment and comparative example 2, it can be seen that the silicon carbide coating can effectively improve the mechanical properties of the carbon fiber, and at the same time, it also has a certain promoting effect on improving the thermal insulation performance; by comparing the embodiment and comparative example 3, it can be seen that under high temperature and high pressure, the viscose-based fiber is modified by carbon deposition, so that the carbon from methane cracking can be deposited in the pores of the viscose-based carbon fiber, thereby improving the density of the fiber; by comparing the embodiment and comparative example 4, it can be seen that the carbon fiber is oxidized at high temperature in a water vapor environment to form a large number of oxygen-containing groups on the surface, which is beneficial to the combination of silicon carbide whiskers and carbon fiber; by adjusting the process in the comparative example, it is intended to prove the influence of various process parameters on product performance. The product prepared by the method of the present invention has good mechanical strength.
[0097] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for preparing a viscose-based fiber thermal insulation composite material, characterized in that: The method comprises: 1) Take viscose raw silk, place it in a tubular furnace, calcine it at high temperature under nitrogen protection to remove impurities, then pass a mixed gas of methane and nitrogen into it, and deposit carbon at high temperature to obtain surface densified carbon fiber; 2) A mixture of water vapor and nitrogen is introduced into a tube furnace for high-temperature oxidation; 3) placing the product of step 2 in a plasma chemical vapor deposition device, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, growing silicon carbide whiskers on the surface of the carbon fiber, and obtaining a carbon fiber with silicon carbide whiskers deposited on the surface; 4) The carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane, taken out and dried, placed in a tube furnace, and calcined at high temperature under nitrogen protection to obtain silicon carbide-coated carbon fiber; 5) placing the carbon fiber obtained in step 4 in a plasma chemical vapor deposition device again, using a mixed gas of tetramethylsilane and hydrogen as a reaction gas, and growing silicon carbide whiskers on the surface of the silicon carbide coating layer; 6) mixing resorcinol, formaldehyde, deionized water and sodium carbonate to obtain a phenolic resin precursor solution; mixing the carbon fiber obtained in step 5 with the precursor solution, heating to prepare a gel, and drying to obtain a xerogel; 7) placing the dry gel from step 6 in a tubular furnace, carbonizing it at high temperature under nitrogen protection, and then graphitizing it at high temperature under nitrogen protection to obtain a viscose-based fiber thermal insulation composite material.
2. The preparation method according to claim 1, characterized in that: In the step 1, viscose raw yarn is taken, put into a tubular furnace, nitrogen is introduced, the temperature is raised to 1000-1200°C, and high-temperature calcination is performed for 2-4 hours to remove impurities, and then a mixed gas of methane and nitrogen is introduced, wherein methane accounts for 40-55% of the volume of the mixed gas, the pressure in the furnace is adjusted to 1.5-3.0Mpa, and high-temperature calcination is performed for 6-10 hours to obtain surface densified carbon fiber.
3. The preparation method according to claim 1, characterized in that: In step 2, the temperature in the tube furnace is lowered to 800-900° C., a mixed gas of water vapor and nitrogen is introduced, wherein the water vapor accounts for 15-25% of the volume of the mixed gas, and the mixture is kept at this temperature for 2-4 hours, and then cooled to room temperature and taken out.
4. The preparation method according to claim 3, characterized in that: In the step 3, the product of step 2 is placed in a plasma chemical vapor deposition device, a mixed gas of tetramethylsilane and hydrogen is used as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10-15%, the working temperature is 800-900° C., the working gas pressure is 100 Pa, the plasma power is 100 W-150 W, and the growth time is 30-60 min, silicon carbide whiskers are grown on the surface of the carbon fiber, and carbon fiber with silicon carbide whiskers deposited on the surface is obtained.
5. The preparation method according to claim 1, characterized in that: In the step 4, the carbon fiber obtained in step 3 is immersed in a xylene solution of polycarbosilane with a molecular weight of 1000-1200, wherein the concentration of polycarbosilane is 8-10wt%, taken out and dried, placed in a tubular furnace, introduced with nitrogen, heated to 1400-1500°C, and calcined at high temperature for 6-10h to obtain silicon carbide-coated carbon fiber.
6. The preparation method according to claim 1, characterized in that: In the step 5, the carbon fiber obtained in the step 4 is placed in a plasma chemical vapor deposition device again, and a mixed gas of tetramethylsilane and hydrogen is used as a reaction gas, wherein the volume percentage of tetramethylsilane in the mixed gas is 10-15%, the working temperature is 800-900° C., the working gas pressure is 100 Pa, the plasma power is 100 W-150 W, and the growth time is 30-60 min, and silicon carbide whiskers are grown on the surface of the silicon carbide coating.
7. The preparation method according to claim 1, characterized in that: In the step 6, resorcinol, formaldehyde, deionized water and sodium carbonate are mixed uniformly in a molar ratio of 1:2:15-20:0.001-0.002 to obtain a phenolic resin precursor solution; the carbon fiber obtained in step 5 and the precursor solution are mixed in a mass ratio of 1:3-4, and then vacuumed to a vacuum degree of more than 0.05Mpa, heated at 50-60°C for 20-30h to obtain a gel, and dried at 100°C to obtain a dry gel.
8. The preparation method according to claim 1, characterized in that: In the step 7, the dry gel of step 6 is placed in a tubular furnace, nitrogen is introduced, the temperature is raised to 1200-1400° C., high-temperature carbonization is performed for 10-16 hours, and then the temperature is raised to 1800-2000° C., high-temperature graphitization is performed for 0.5-1 hour to obtain a viscose-based fiber thermal insulation composite material.
9. A viscose-based fiber thermal insulation composite material, characterized in that: The material is prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of silicon carbide reinforced carbon fiber composite materials
CN104591764A
Method for preparing diamond coating on cemented carbides surface
CN105200392A
Preparation method of high-density, low-heat-conductivity and high-temperature-resistance carbon fiber reinforced silicon carbide / glass carbon composite material vacuum insulation plate
CN108068432A
High-temperature-resistant ceramic matrix composite interface composite coating and preparation method
CN111517810A
Carbon aerogel composite material and method for preparing carbon aerogel composite material by modifying carbon fibers through chemical vapor infiltration process
CN117923936A